Smart Writing in Digital Political Discourse - Al klbani, Saleh bin Sulaiman (Dirasat: Human and Social Sciences, 2025)
Objectives: This research aims to demonstrate the representations of violence in speech act theory. It argues that when a speaker speaks, they act, perform, and influence; they are not merely providing reports or statements subject to truth and falsehood standards, but rather intend to create an impact on their audience. The study, based on its corpus, sought to scrutinize and confirm the types of forces used in digital political discourse during a crisis in the Middle East. Methods: The research employed a pragmatic approach, starting with an examination of the corpus, then categorizing it into words, images, and clips, each containing a diverse set. Results: Through the corpus, the research revealed that everyday natural communications are capable of mobilization and that this discourse is a linguistic material that requires and deserves examination, analysis, and the uncovering of its fallacies, strategies, methods, genres, and impacts. The research confirmed that violence through speech acts in digital discourse affects politics from various aspects. Conclusions: The patterns of forces have evolved, not in terms of soft power and developments in dealings, but through language and its use in managing conflicts with both violence and non-violence, which the research refers to as politically smart writing.